Port of Batam Revisited: Options in The Middle of Market and Policies Dynamics - Fathony, Haemiwan Zumar; Wicaksono, Agung (Jurnal Manajemen Teknologi, 2012)
Despite having similar inherited factors such as strategic location doesn’t make the Port of Batam to have similar performance and capability like its neighbouring ports in Malaysia and Singapore. There are policy issues that hindered the development of the necessary resources to tap the lucrative transhipment market in the Malacca Strait. The past positioning as the utility factor for the local industry has back fired when the local demand hasn’t grow strong enough. It also has the impact on the lack of resources including the land for container handling and storage. Due to the limited land-based resources, The Port shall look at the opportunities in other area, its water. The Port may look at and enter the related business in the water such as ship to ship transfer and anchoring business. Port of Batam may also look at the terminaling opportunity on the water, i.e. by implementing the floating container, storage, and transhipment terminal (FCSTT) concept along with the implementation of the same concept in the form of floating, storage and offloading (FSO) for the liquid and gas cargo, thus tapping the oil transfer market in the Malacca Strait as well.Keywords: Port of Batam, Malacca Strait, sea port business, transhipment, floating container terminal